If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7z + -11 = -3 + 9z Reorder the terms: -11 + 7z = -3 + 9z Solving -11 + 7z = -3 + 9z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-9z' to each side of the equation. -11 + 7z + -9z = -3 + 9z + -9z Combine like terms: 7z + -9z = -2z -11 + -2z = -3 + 9z + -9z Combine like terms: 9z + -9z = 0 -11 + -2z = -3 + 0 -11 + -2z = -3 Add '11' to each side of the equation. -11 + 11 + -2z = -3 + 11 Combine like terms: -11 + 11 = 0 0 + -2z = -3 + 11 -2z = -3 + 11 Combine like terms: -3 + 11 = 8 -2z = 8 Divide each side by '-2'. z = -4 Simplifying z = -4
| -8x-8x=64 | | -3q+r+2-q-6r= | | 8.2=2.8(3x-2) | | a^2+9ab-10b^2=0 | | 4x-18=-7(8-6x) | | [x+5]=42 | | 0=x^2+11x-34 | | x^2+0.8x-4.16=0 | | -x=(-2/9) | | n-10=5/6-7-1/3n | | 45+2x=180 | | 5q+2y-1+3q-5y= | | 3d+2(5d+4)=47 | | -2(8+3a)=24-a | | y^8-32y^4+256=0 | | u^2+3uv=0 | | -3x^2+525x-19602=0 | | log(8)(-3s+12)=log(8)(-7s+4) | | 6(4+4a)=24-4a | | m^2-11mn+10n^2=0 | | p^2+4p-43=0 | | 3n^3+21n^2-5n-35=0 | | 16-5x=x-26 | | a^2+10ab+9b^2=0 | | x(x+2)-8=2x+17 | | 30u^4v^3/5u^5v^3 | | 450x=380+3500 | | -96=-3(-5x+7) | | X^2-4=22 | | x-8.8=-5.8 | | -7x+5(1x-3.6)=8x-3200 | | -7x+5(1x-3.6)=4x-3200 |